Production of citric acid from sugarcane molasses by Aspergillus niger using submerged fermentation - Almakki, Asma; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed (2019)
Citric acid (CA) has a high demand due to its various uses in the food and pharmaceutical industries. However, the natural supply of CAis minimal compared to its growing industrial demand. The increasingdemand for CA can be fulfilled by using biotechnological processes. This study utilized liquid state bioconversion by Aspergillus niger for CA production using sugarcane molasses as the primary substrate. Sugarcane molasses which is agricultural waste consists of significant proportion of organic matters such as lipids and carbohydrates. This makes sugarcane molasses as a potential and alternative source of producing CA at a lower cost. In this study, statistical optimization was applied to improve CA production using submerged fermentation in shake flasks. Aspergillus nigerwas cultured in potato dextrose agar. Then, inoculum spores were introduced into the fermentation media for a specific duration according to the experimental design from Central Composite Design (CCD) tool under Response Surface Methodology (RSM) in Design Expert 6.0 software. Three parameters were chosen to be optimized at 32⁰C i.e.agitation rate (160, 80, 200 rpm), substrate concentration (47, 60, 73%) and fermentation time (24, 72, 120 h). High Performance Liquid Chromatography (HPLC)and Fourier-transform infrared spectroscopy(FTIR) analyses were conducted to measure CA yield. The optimization study showed that the media incubated for 72 hours with a substrate concentration of 60% and an agitation speed of 180 rpm produced the highest CA yield(21.2 g/L).The analysis of variance (ANOVA) also showed that CCD quadraticmodel was significant with P-value< 0.0104 and R2is0.8964